ENSURING YOUTH PARTICIPATION AND ITS PROSPECTS IN DEVELOPING EFFECTIVE PUBLIC ADMINISTRATION IN THE NEW UZBEKISTAN (International Congress on Economics, Management and Business Studies, 2026)
This article provides a scientific analysis of ensuring youth participation and its prospects in developing effective public administration in the context of the New Uzbekistan. It also highlights that one of the priority tasks in building the New Uzbekistan is the modernization of the public administration system, ensuring its transparency and efficiency.
Keywords: New Uzbekistan, public administration, youth policy, civil society, efficiency, human resource potential.